Produtividade da mão de obra na execução de instalações prediais hidráulicas e sanitárias - Monteiro, Paulo Roberto Moreira (2017)
The construction industry did not follow the others industries as regards developments of the labor resources and presents low levels productivity. The labor productivity is mainly responsible for the rhythm of work, therefore, know the productivity of a task is of extreme importance and in possession of this information, if reliable, various benefits can be achieved. Specifically, in the execution of the building systems, this information is very scarce due to the difficulties of data collection of fragmented services, added to the frequent outsourcings adopted by builders companies. This work aims to deepen the knowledge on labor productivity of execution of Sanitary and Plumbing Building Systems when these efforts are applied with management systems involving kits or materials and techniques not measured yet. Among the results obtained are the measurement of the labor of productivity of the Sanitary and Plumbing Building Systems executed with Polypropylene Random Copolymer, the comparative analysis of this with other materials available in the market with the same destination of use, and the advances on the productivity advantages of the pre-production and subsequent installation of hydraulic kits that, if in ideal situations of context reached productivity 3.5 times greater than labor productivity of the conventional system, in the most unfavorable scenarios obtained timid gains of productivity, demonstrated as a whole an expressive gain of efficiency. In this way, the main contribution of this work consist in the possibilities the data collected allow in the field of decision making concerning the constructive method of Sanitary and Plumbing Building Systems with Polypropylene Random Copolymer and encourage the adoption of models that involve rationalized production.